Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Make a Match dan Minat Belajar terhadap Hasil Belajar Biologi Peserta Didik Kelas X MIPA SMA Negeri 4 Bantaeng - Sahodding, Sahodding; Hala, Yusminah; Palennari, Muhiddin (Universitas Negeri Makassar, 2023)
The study aims to examine (1) the learning outcomes based on the interests taught by using the Cooperative Learning Model of Make a Match type and the conventional learning, (2) the differences in learning outcomes based on the interests between those taught by using the Cooperative Learning Model of Make a Match type and the conventional one. This type of study is a true experimental research design using a 2x2 factorial design. The research population was all grade X MIPA at SMAN 4 Bantaeng for academic year 2021/2022 with 141 people. The sampling was conducted by using simple random sampling technique and the class selected was grade X MIPA 2. The hypothesis testing was conducted by using the SPSS 21.0 program with Ancova two way analysis. The results of the study reveal that (1) the learning outcomes based on the interests taught by using the Cooperative Learning Model of Make a Match type is better than students taught by using conventional learning model, (2) there is no significant difference in learning outcomes based on interests between those taught by using the Cooperative Learning Model of Make a Match type and the conventional learning model.